Penggunaan Laporan Keuangan Untuk Melihat Gambaran Kemandirian Keuangan Daerah Kabupaten dan Kotamadya di Pulau Sumatera - Halkadri Fitra (Universitas Negeri Padang, 2018)
The purpose of this study is to determine the financial independence of regencies and cities on the island of Sumatra from 2012 to 2016. This type of research is classified as qualitative descriptive with data collection techniques used is the method of secondary data documentation of financial reports, budget realization reports in 120 regencies and 34 cities. The results showed that the financial independence of regencies and municipalities in the island of Sumatra is still in very low category with an average value of 8.63% with the pattern of central and local financial relationship is instructive. The regencies with the highest regional financial independence ratios in 2012 to 2016 are Karimun regency in Riau Islands Province while the city area is Medan City of North Sumatra Province from 2012 to 2013 and Batam City of Riau Islands Province from 2014 to 2016Keywords: city, regency, regional finance, independence ratio